Long-Baseline Neutrino Oscillation Experiments. (6th March 2013) - Feldman, G. J.; Hartnell, J.; Kobayashi, T.
Abstract : A review of accelerator long-baseline neutrino oscillation experiments is provided, including all experiments performed to date and the projected sensitivity of those currently in progress. Accelerator experiments have played a crucial role in the confirmation of the neutrino oscillation phenomenon and in precision measurements of the parameters. With a fixed baseline and detectors providing good energy resolution, precise measurements of the ratio of distance/energy (L / E ) on the scale of individual events have been made and the expected oscillatory pattern resolved. Evidence for electron neutrino appearance has recently been obtained, opening a door for determining the CP violating phase as well as resolving the mass hierarchy and the octant of θ 23 ; some of the last unknown parameters of the standard model extended to include neutrino mass.